The Effect of Financial Knowledge And Internal Locus Of Control On MSMEs Performance: The Mediating Role of Qris Adoption In Sentra IKM Gresik - Muhammad Syihabuddin Ridho; Tri Kartika Pertiwi; G. Oka Warmana (UNIVERSITAS PAKUAN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a critical role in contributing to national economic growth. This study aims to examine the influence of financial knowledge and internal locus of control on MSMEs performance through the QRIS Adoption as a mediating variable among MSMEs in Sentra IKM, Gresik Regency. This research uses a quantitative approach, utilizing purposive sampling with a sample size of 89 respondents. Data analysis and hypothesis testing were conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that financial knowledge significantly enhances both MSMEs performance and QRIS adoption. However, internal locus of control does not directly affect MSMEs performance, though it positively influences QRIS adoption. While QRIS adoption significantly impacts MSMEs performance, it fails to mediate the relationship between financial knowledge and MSMEs performance. Conversely, QRIS adoption successfully mediates the effect of internal locus of control on MSMEs performance.